HUKUM PROGRESIF SEBAGAI PARADIGMA HUKUM DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA - Muhammad Irwan; Slamet Sampurno Soewondo; Julianto Jover Jotam Kalalo (SOCIETAS, 2018)
This study aims to determine progressive law enforcement in an effort to eradicate corruption in Indonesia and the application of progressive law in the context of combating corruption in Indonesia. The type of research used, namely normative legal research. Data is obtained through primary legal materials, secondary legal materials, and tertiary legal materials. Data analysis was carried out qualitatively and presented descriptively. The results of this study indicate that (1) progressive law enforcement in the effort to eradicate corruption acts lies in the activities of aligning the values contained in the community then realizing those values into reality, where in its application is influenced by several factors including legal substance, structure law, legal culture, professionalism, and leadership. (2) A criminal act of corruption is a criminal act which is categorized as an extraordinary crime due to the impact of a very wide corruption, which is concerning the welfare of the people. KPK as a law enforcer must also be able to carry out more progressive and massive prevention and repression efforts so that it can minimize or even eradicate the nation's problems completely. In this case too, the KPK does not work alone, it also requires an active role of the community in carrying out preventive efforts for the realization of an anti-corruption community. Keywords: Law, Corruption, Progressive, Criminal.